2017
DOI: 10.1620/tjem.243.219
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of SMYD3 Is Predictive of Unfavorable Prognosis in Hepatocellular Carcinoma

Abstract: SET and MYND domain-containing protein 3 (SMYD3) is a kind of histone lysine methyltransferase, responsible for transcriptional activation as a member of an RNA polymerase complex. The ectopic expression of SMYD3 is proved to promote the progress of many kinds of cancers. In hepatocellular carcinoma (HCC), SMYD3 was demonstrated to promote the proliferation and metastasis of HCC cell lines, but the clinical significance of SMYD3 has not been elucidated. In the present study, we detected the expression of SMYD3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 22 publications
3
11
0
Order By: Relevance
“…SMYD3 protein expression levels appear to convey an unfavorable prognosis in HCC. In a cohort of 100 HCC cases, Fei et al showed that high SMYD3 expression correlated with HCC tumor size and poor overall survival [33]. In this study, patients with low expressing SMYD3 tumors had a 5-year overall survival rate of 48.7%, in contrast to the highly expressing SMYD3 group of 29.6%.…”
Section: Hepatocellular Carcinomamentioning
confidence: 49%
“…SMYD3 protein expression levels appear to convey an unfavorable prognosis in HCC. In a cohort of 100 HCC cases, Fei et al showed that high SMYD3 expression correlated with HCC tumor size and poor overall survival [33]. In this study, patients with low expressing SMYD3 tumors had a 5-year overall survival rate of 48.7%, in contrast to the highly expressing SMYD3 group of 29.6%.…”
Section: Hepatocellular Carcinomamentioning
confidence: 49%
“…SMYD3 knockdown increases cisplatin sensitivity in tumor cells. SMYD3 is often highly expressed in cancer tissues and is closely associated with malignancy and poor prognosis of patients (29,30). However, the association between SMYD3 expression, chemotherapy and its outcomes remains unclear.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro evidence indicates that SMYD3 expression is up-regulated in HCC cell lines 12,32 . SMYD3 expression was analyzed in HCC tissues, and upregulation was significantly associated with an unfavourable prognosis of HCC 33,34 . SMYD3 mRNA expression was upregulated in HCC tumor compared to adjacent non-tumor tissues, providing further evidence of a role of SMYD3 in HCC development.…”
Section: Discussionmentioning
confidence: 99%